Herramienta educativa MOODLE y su incidencia en la enseñanza de los estudiantes de bachillerato de ciencias de la Unidad Educativa Babahoyo del periodo académico 2021-2022 - Alcivar Castro, Damarys Tamara (2022)
The research project carried out lies in obtaining information which allowed us to know everything about the Moodle educational tool and its impact on the teaching of high school science students in the evening section of the Babahoyo Educational Unit. It should be considered, on the other hand, that for the development of the project the execution of the mixed research method was carried out, the modality that was carried out was field research and bibliographic consultations of secure sources for the elaboration of the theoretical framework, the types of research applied were descriptive and explanatory, the types of research used were analytical, synthetic and deductive. In effect, the techniques that were used for the development of the project was the survey carried out through the Google form, the instruments used were the bibliographical research and a bank of 10 questions asked of the students, which allowed us to obtain all the information necessary to study the current context with respect to problems raised exposed in the institution. Therefore, with the results obtained, it was possible to evidence the different answers that the students showed, which, in one of the questions asked, about whether the educational institution would have carried out training, it was evident that the majority of the respondents I indicate that the educational institution has not carried out training for the correct use of the Moodle Educational Tool. Finally, it was found that the students do not know how to use the educational tool correctly, therefore, there was a need to design a content plan on all the resources that the tool entails, which will be delivered to the institution so that the teachers teach the training of the students and thus generate that the students can make a correct use of the tool and through this strategy they can improve the teaching-learning process in the Babahoyo Educational Unit.